Immunomodulatory potential of mesenchymal stem cell-derived extracellular vesicles: Targeting immune cells - Liu, Xi; Wei, Qian; Lu, Lu; Cui, Shengnan; Ma, Kui; Zhang, Wenhua; Ma, Fang; Li, Haihong; Fu, Xiaobing; Zhang, Cuiping (Frontiers in Immunology, 2023)
Various intractable inflammatory diseases caused by disorders of immune systems have pressed heavily on public health. Innate and adaptive immune cells as well as secreted cytokines and chemokines are commanders to mediate our immune systems. Therefore, restoring normal immunomodulatory responses of immune cells is crucial for the treatment of inflammatory diseases. Mesenchymal stem cell derived extracellular vesicles (MSC-EVs) are nano-sized double-membraned vesicles acting as paracrine effectors of MSCs. MSC-EVs, containing a variety of therapeutic agents, have shown great potential in immune modulation. Herein, we discuss the novel regulatory functions of MSC-EVs from different sources in the activities of innate and adaptive immune cells like macrophages, granulocytes, mast cells, natural killer (NK) cells, dendritic cells (DCs) and lymphocytes. Then, we summarized latest clinical trials of MSC-EVs in inflammatory diseases. Furthermore, we prospect the research trend of MSC-EVs in the field of immune modulation. Despite that the research on the role of MSC-EVs in regulating immune cells is in infancy, this cell-free therapy based on MSC-EVs still offers a promising solution for the treatment of inflammatory diseases.